The Effect of Group Size on Cognitive and Behavioural Students' Engagement - Laaziz, Youssef; Chemsi, Ghizlane; Radid, Mohamed (International Journal of Emerging Technologies in Learning (iJET), 2023)
The size of the group is an important subject to discuss, especially in light of the challenges that appear with the trend toward large institutions with large student bodies in higher education, including the quality of student integration and the quality requirements that higher education must meet in light of the high qualifications demanded by the world of employment. In this study, we examine the effect of learning-group size on students’ cognitive and behavioral engagement. In a quantitative approach, a questionnaire survey is used to collect data from 234 students at the Hassan II University in Casablanca. The purpose of this research is to demonstrate the influence of group size on students’ cognitive and behavioral engagement. The participants were separated into 140 students in large groups and 94 small groups. A questionnaire measured the impact of group size on participants’ cognitive and behavioral engagement and had a Cronbach’s alpha value of 0.9. According to the study’s findings, group size should be taken into account because it affects most factors related to cognitive and behavioral engagement. To increase student involvement and boost their academic achievement, it is advised that more empirical research should be done in order to develop pedagogical strategies to control this difference much better.